Efectos de la fibra soluble e insoluble sobre los parámetros digestivos en cobayos en etapa de post - destete. - Córdova Encalada, Natali Silvana (2024)
Dietary fiber is an essential component in guinea pig diets, has different effects depending on its solubility and is crucial in intestinal health. This research evaluated the effects of the inclusion of different levels of soluble and insoluble dietary fiber on digestive parameters in post-weaning guinea pigs. With 40 weaned guinea pigs Type A1 of 15 days of age, randomly distributed in four experimental diets with levels of soluble fiber (SF) and insoluble fiber (IF). As sources of insoluble fiber, wheat bran and King Grass, citrus pectin as soluble fiber, for 10 days, diet one 4.48 % Low FS x 29.0% BFI; diet two 12.0% High FS x 28.0% BFI; diet three 6.52% BFS x 35.5% AFI; and diet four 12.0 % AFS x 35.8% AFI. Absolute and relative weight of digestive organs, absolute and relative length of small intestine and pH of stomach and cecum were evaluated. Data were processed by analysis of variance (InfoStat) and Fisher's LSD test was used to compare means. The results showed that the total digestive tract variable had a significant difference in relative weight (p=0.0057), while in pH with the inclusion of insoluble fiber it was significant for stomach (p=0.028) and for cecum (p=0.001), and also with the inclusion of soluble fiber with a p=0.008. No significant differences were detected in the interaction of soluble and insoluble fiber on the parameters. It is concluded that insoluble fiber is more effective in improving digestive parameters in post-weaning guinea pigs, contributing to better digestive health and growth, while soluble fiber influences the regulation of cecum pH, which determines that both types of fiber should be considered in the formulation of diets to optimize digestion.